Assessment of the absorbed dose after exposure to surgical smoke in an operating room. (1st August 2020) - Van Gestel, Ellen A.F.; Linssen, Eveline S.; Creta, Matteo; Poels, Katrien; Godderis, Lode; Weyler, Joost J.; De Schryver, Antoon; Vanoirbeek, Jeroen A.J.
Abstract: Surgical smoke produced by electrosurgery contains various chemical substances such as volatile organic compounds (VOCs) and polycyclic aromatic hydrocarbons (PAHs). The aim of this study is to investigate airborne concentrations of VOCs and PAHs during electrosurgery in an operating room, in relation to metabolites in urine in order to assess the absorbed dose. A 5-day exposure study was set up in a general surgery operation room including surgeons, scrub assistants and circulation nurses (n = 15). Stationary and personal air sampling for VOCs and PAHs were carried out. Pre-, mid- and end-shift analysis of urinary S-phenylmercapturic acid (SPMA), o-cresol, mandelic acid and 1-hydroxypyrene was performed to assess the internal exposure to respectively benzene, toluene, styrene and PAHs. Several VOCs (styrene, ethyl benzene, benzene and toluene), ranging from 0.7 to 3.27 μg/m 3 were detected in the air samples, along with one PAH (naphthalene, ranging from 0.012 to 0.39 μg/m 3 ). There was no significant correlation between air monitoring and urinary biomonitoring. O-cresol levels were increased, especially among assistants and nurses at mid- and end-shift, exceeding current biological exposure indices several times. External and internal exposure for assistants and nurses was substantially more, compared to surgeons. This study confirms the presence of VOCs and PAHs in surgical smoke and shows the presence of their metabolites in urine, but the association is unclear. Urinary biomonitoring shows especially high concentrations of o-cresol.